Efektivitas Bimbingan Kelompok Untuk Meningkatkan Regulasi Emosi Remaja Dari Keluarga Single Parent Di SMP Negeri 7 Muaro Jambi - Kurniati, Kurniati; Amanah, Siti; Fitriana, Fitriana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2026)
Adolescents from single-parent families are one group that is vulnerable to experiencing difficulties emotional regulation. One potential way to support adolescent emotional regulation in schools is through group counseling, which are an effective method of providing social and emotional support. The purpose of this study was to determine the effectiveness of group counseling in improving the emotional regulation of adolescents from single-parent families. The research was conducted at SMP Negeri 7 Muaro Jambi with a sample of six ninth-grade students selected based on specific criteria related to emotion regulation difficulties. The research was conducted using a quantitative approach with a pre-experimental one-group pretest-posttest design. Data collection was carried out by administering a modified Difficulties Emotion Regulation Scale (DERS), which was then analyzed using a T-Test and N-Gain Scale The results showed that the average pretest score was 68.7, with 46% of the sample falling into the low category. Meanwhile, the average posttest score was 103.3, with 69% of the sample falling into the high category. The Paired Sample Test results showed a Sig. (2-Tailed) value of 0.004, with an NGS calculation of 0.426, which falls into the moderate category. Based on the decision-making criteria, there was a significant difference in the level of emotional regulation before and after group counseling was provided. Thus, group counseling are effective in improving the emotional regulation of adolescents from single-parent families at SMP Negeri 7 Muaro Jambi.